VIDEO AS TEACHING MEDIA TO IMPROVE STUDENTS’ MOTIVATION IN LEARNING ENGLISH FOR THE ELEVENTH GRADE OF IPS 2 MA NEGERI RENGEL TUBAN - . Muktamir (IKIP PGRI Bojonegoro, 2017)
Abstract: Video as Teaching Media to Improve Students’ Motivation in Learning English for the Eleventh Grade of IPS 2 MA Negeri Rengel Tuban. The individual learning success is influenced by many factors. Motivation as a part of the factors gives strong influence to the students in their activities in learning English. This study was designed to improve the students' motivation by using video. In this study we use short film as an instructional media by implementing three steps in teaching process, i.e: pre- activity, whilst activity and post activity. The study was Classroom Action Research (CAR). The subjects were the eleventh grade of IPS 2 MA Negeri Rengel Tuban in the 2016-2017 academic years consisting of 32 students. The instruments used in this study consist of test, field notes, observation sheets, and questionnaire. The findings showed that the use of video can improve the students' motivation. It can be seen from questionnaire; the findings indicated that the students increased their intrinsic motivation and extrinsic motivation. It can be seen from the increasing of the students' motivation in preliminary study and the result in cycle 1 and cycle 2. The students' intrinsic motivation in preliminary was 53.4 %, in cycle 1 was 68.8 % and in cycle 2 was 85.4%. The students' extrinsic motivation in preliminary was 51.5%, in cycle 1 was 78.6% and in cycle 2 was 89.6%.Keywords: Video, teaching media, motivation.Abstrak: Video sebagai Media Pembelajaran untuk Meningkatkan Motivasi Belajar Bahasa Inggris para Siswa Kelas XI IPS 2 MA Negeri Rengel Tuban. Keberhasilan beelajar indivisu sangat dipengaruhi oleh banyak factor. Motivasi sebagai bagian dari factor-faktor yang memberikan penaruh yang kuat bagi para siswa padaaktivitas pembelajaran Bahasa inggris. penelitian ini di desain untuk meningkatkan motivasi beljaran para siswa dengan menggunakan video. Pada penelitian ini kita menggunakan film pendek sebagai medi pembelajaran dengan menerapkan tiga langkah dalam proses pengajaran. Penelitian ini adalah Penelitian Tindakan Kelas. Subyek penelitian ini adalah parasiswa kelas sebelas IPS 2 MA Negeri rengel Tuban pada tahun pelejaran 2016/2017 yang terdiri atas 32 siswa. Instrumen yang digunakan dalam penelitian ini adalah tes, catatan lapangan, lembar observasi dan kuisioner. Hahil penelitian ini menunjukkan bahwa penggunaan video dapat meningkatkan motivasi para siswa. Hal ini dapat dilihat dari hasil pengisian kuesioner; hasil penelitian mengindikasikan bahwa motivasi instrinsik dan ekstrinsik para siswa mengalami peningkatan. Hal ini bisa bilihat dari hasil pembelajaran pada siklus 1 dan 2. Motivasi instrinsik siswa adalah pada saat studi pendahuluan adalah 53.4%, dan meningkt pada siklus 1 menjadi 68.8% dan di siklus 2 meningkat menjadi 85.4%. Motivasi ekstrinsik para siswa pada pre-studi adalah 51.5% dan pada siklus 1 adalah 78.6% dan hasil setelah siklus 2 adalah 89.6%.Kata kunci: Video, media pengajaran, motivasi.